The fall of Great Moravia
1 online resource.
Keywords: The excavated foundations of a ninth-century sacral building in the northeastern suburb of Pohansko, an important centre of Great Moravia, and especially the find of the nobleman's grave H 153, has focused scholarly attention onto the nature of the Mojmirid state and the reasons behind its sudden disintegration. In this volume, a group of archaeologists, historians and a natural scientist aim to incorporate this remarkable discovery into the wider frameworks of Moravian power, society, and culture, and thereby arrive at some surprising conclusions. Contributors: are Stefan Eichert, David Kalhous, Pavel Kouřil, Jiří Macháček, Vladimír Sládek, Ivo Štefan, Martin Wihoda, Roman Zehetmayer.